"أثر المناخ التنظيمي على الإستغراق الوظيفي لأداء العاملين دراسة ميدانية بمؤسسة بريد الجزائر – فرع الوادي- " - حسين, حميداتو; مختار, قريشة; عمر, الشايب; عبد العالي, علال (جامعة الوادي - University of Eloued, 2023)
" هدفت هذه الدراسة إلى بيان أثر المناخ التنظيمي بمختلف أبعاده: مشاركة العاملين، القيادة، الحوافز الاتصال، طبيعة العمل، في تنمية الاستغراق الوظيفي لدى العاملين بمؤسسة بريد الجزائر فرع الوادي. تم اختبار فرضيات الدراسة على عينة مكونة من (50) عامل وذلك باستخدام الانحدار الخطي المتعدد اعتمادا على الحزمة الإحصائية للعلوم الاجتماعية ( SPSS). خلصت الدراسة إلى أنه يوجد أثر ذو دلالة إحصائية لأبعاد المناخ التنظيمي في تنمية الاستغراق الوظيفي لأبعاد مشاركة العامين، وطبيعة العمل، القيادة، الحوافز، الاتصال أثر على المتغير التابع الاستغراق الوظيفي، كما تم تقديم اقتراحات عملية وآفاق مستقبلية للدراسة. " "This study aimed to investigate the impact of the organizational climate in its various dimensions: employee participation, leadership, communication incentives, nature of work, on the development of job involvement among employees of Algeria Post Corporation, El-Wadi branch. The study hypotheses were tested on a sample of (50) workers, using multiple linear regression based on the statistical package for social sciences (SPSS) The study concluded that there is a statistically significant effect of the dimensions of the organizational climate in the development of job involvement for the dimensions of the participation of the two years, and the nature of work, leadership, incentives, and communication. "
Keywords: المناخ التنظيمي، مشاركة العاملين، القيادة، الحوافز، الاتصال، طبيعة العمل، الاستغراق الوظيفي.: organizational climate, employee participation, leadership, incentives, communication, nature of work, job involvement.